PENGARUH PENDIDIKAN MULTIKULTURAL DAN PENDIDIKAN KARAKTER TERHADAP SIKAP TOLERANSI SISWA SMA PANCASILA SUNGAI KAKAP - Ramadhan, Iwan; Salim, Izhar; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research entitled "The Effect of Multicultural Education and Character Education on Student Tolerance at SMA Pancasila Sungai Kakap". The method used is quantitative, data collection techniques with questionnaires, the number of 86 samples using random sampling. Testing data analysis using validity test, reliability, classical assumption test and multiple linear regression test. The statistical results show that the value of t arithmetic <t table (0.289 <1.671), then Ha rejected. So concluded multicultural education (X1) in partial no significant effect on the attitude of tolerance. On the character education variable (X2) Because the value of t arithmetic> t table (7,882> 1,671), then Ha received. So concluded Character education (X2) partially significant effect on the attitude of tolerance. The result of Fcount in column F that is 30,763 look for F value table according to statistical calculation with df2 (n-k-1) or 86-2-1 = 83, with significance 0,05 hence known value F table is 3,29. Because the value of F arithmetic is 30.763 and 62.121, F table is 3.29 then the value of F arithmetic> F table. Thus Ho is rejected, which means that multicultural education and character education simultaneously have a significant effect on tolerance.Â Keywords: Multicultural Education, Character Education and ToleranceÂ Â